Contemporary Modes of Remembering the Holocaust — How and Why? (KULT_online, 2023)
Trauma and Memory: The Holocaust in Contemporary Culture edited by Christine Berberich explores the different ways in which the Holocaust is represented and commemorated in contemporary cultures, including fiction, films, museums and social media. The edited volume compels us to reflect on how the Holocaust can be remembered without forgetting why we need to do so. Contributions problematize newer ways of remembering and discuss if and how ideas regarding ‘correct’ and ‘incorrect’ forms of commemoration and representation are gradually changing in the present.